An integrated methodology model for smart mobility system applied to sustainable tourism - Carlo Amendola; Simone La Bella; Gian Piero Joime; Fabio Massimo Frattale Mascioli; Vito Pietro (Administrative Sciences, 2022)
This work aims to analyze the impact of technological eco-innovation on the modernization and development of a local area. The role of eco-innovation would be to stimulate an innovative environment and spur a development of the territory and economic districts, and the diffusion of said particularities among wider geographic contexts, hence allowing a globalization model more observant of local specificities, and thus an open system able to develop economic and cultural exchange respecting local particularities. In recent years, smart city has asserted itself as a general model for the city of tomorrow, and sustainability has become a focal point in urban development policies. In this paper, we investigate how an integrated and intermodal methodology for the development of smart mobility systems-the European project "Life for Silver Coast"-is impacting the modernization and development of an Italian coastal area in Tuscany. The main focus of our paper is to understand how an integrated mobility network allows a transition toward a sustainable form of social relationship and a new economic pattern and could represent the starting point for a spatial, relational and institutional reorganization process that would lead to a change in the production and management dynamics of the local ecosystem concerning cultural, social and economic issues.
Keywords: 350; smart city; sustainable tourism; smart mobility